Designing a Website Mockup for PT. XYZ Company Profile - Suri, Ghea Paulina; Arifin, Nofri Yudi; Larisang, Larisang (Engineering and Technology International Journal, 2024)
The advancement of digital technology has placed greater emphasis on a company's online presence, particularly through a company profile website. This research aims to design a mockup for PT XYZ's company profile website by utilizing a combined approach of primary and secondary data. Primary data will be obtained through interviews with the company management to understand the company's values, communication objectives, and desired design preferences. Meanwhile, secondary data will be used to gain insights into current design trends and best practices in website design. This research method combines qualitative and descriptive approaches, with initial steps focusing on identifying PT XYZ's needs and communication objectives.Based on the interview results, initial design concepts will be developed that reflect the company's identity and consider user needs. By integrating primary and secondary data, this research is expected to produce a mockup design for the company profile website that meets PT XYZ's communication and representation needs, while aligning with current web design standards. The findings of this research are expected to provide practical guidance for PT XYZ in enhancing the company's image through effective and engaging digital media.